How does the state-led megaregion affect local environmental governance? Evidence from China - Ran Jin; Xiaolin Wang (Humanities & Social Sciences Communications)
Abstract What impact do megaregions have on local environmental governance? Previous studies show mixed results due to the varying effects across different types of megaregions. This study investigates how state-led megaregions—specific regional formations in which the central government can use vertical interventions to guide urban development and reshape intergovernmental relations—affect local environmental governance. Using a difference-in-differences model and data from 296 Chinese cities, we find that the establishment of state-led megaregions significantly reduces urban pollution, especially in resource-based cities facing high environmental pressures and in cities with strong economic growth incentives. We identify two key mechanisms: direct effects through reduced information asymmetry in collaborative environmental governance and increased government willingness to invest in environmental protection, as well as an indirect effect driven by economic structural transformation. These findings provide important insights for improving local governance, promoting sustainable economic growth, and reducing pollution under state-led megaregion plans, offering potential applications for achieving the goals of sustainable economic growth (SDG 8) and building sustainable cities (SDG 11) globally.